Strengthening the Role of Sufi Lodges and Tekkes in Promoting Civil Peace in Salah al-Din Governorate (Islamic Sciences Journal, 2025)
Sufi lodges and takayas are important spiritual and social centers that have played a prominent role in spreading the values ​​of tolerance, love, and peaceful coexistence in Islamic societies throughout history. In Salah al-Din Governorate, which has faced security and social challenges, these institutions can effectively contribute to promoting civil peace through their religious, social, and spiritual programs
Keywords: Sufi corners, Sufi lodges, civil peace, Salah al-Din, community coexistence